The Effect of Economic Growth and Inflation and Unemployment Rate on Human Development Index and Poverty in East Kalimantan Province - Fitrah Hitayah; Aji Sofyan Effendi; Muhammad Awaluddin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study aims to determine the Effect of Economic Growth and Inflation and Unemployment Rate on the Human Development Index and Poverty in East Kalimantan Province. Inferential data analysis techniques using Partial Least Squares (PLS). The results of the study indicate that the Human Development Index (HDI) has a significant effect on the unemployment rate in East Kalimantan Province, with a probability value smaller than the specified significance level. There are disparities that need to be considered in development in rural areas to ensure equal opportunities for all residents to achieve a better quality of life. Rural areas still face challenges in access to education and health services, as well as regional disparities in development, which need to be addressed through appropriate and sustainable policies. Assistance programs such as Direct Cash Assistance (BLT), National Health Insurance (JKN), and the Family Hope Program (PKH) have helped reduce the burden on the poor by providing access to basic needs. Efforts to improve the quality of education, health, and infrastructure in rural areas are the main focus to create a more prosperous and independent society. Although there has been progress in poverty alleviation, there are still challenges such as regional inequality, quality of education and health, and economic diversification that need to be addressed. Collaboration between the government, private sector, and civil society is needed to create sustainable and effective solutions to overcome poverty in East Kalimantan. Economic growth, inflation, and unemployment rates are interrelated and significantly affect the Human Development Index and poverty rates in East Kalimantan Province. Therefore, comprehensive and sustainable policies are needed to achieve inclusive and equitable development in this region.